Effects of N-Acetylcysteine in Renal Ischemia/Reperfusion Injury in the Rats - Aydoğdu, Nurettin; Kaymak, Kadir; Yalçın, Ömer (Fırat University, 2005)
Objectives: Free radicals have played an important role in the pathophysiology of severel disease including renal ischemia/reperfusion injury. The aim of this study was to estimate any protective effects of N-acetylcysteine, an antioxidant and the precursor of glutathione synthesis on the tissue damage during ischemia/reperfusion injury of kidney. Materials and Methods: Twenty four female Spraque Dawley rats divided into three groups: Group 1; was given saline intraperitonealy. Group 2; subjected to bilateral renal ischemia followed by reperfusion and saline injected ip 30 min before induction of ischemia. Group 3; is also subjected to bilateral renal ischemia followed by reperfusion and N-acetylcysteine (300 mg/kg) injected intraperitonealy 30 min before induction of ischemia. At the end of the reperfusion period, the rats were sacrificed. Kidney superoxide dismutase, catalase, glutathione peroxidase activities, malondialdehyde and glutathione levels, plasma urea, creatinine, glutathione and malondialdehyde levels were determined. Kidney was also histopathologically examined. Results: İschemia/reperfusion application was increased urea and creatinin levels (p

Amaç: Serbest radikaller, böbrek iskemi/reperfüzyon hasarı gibi birçok hastalığın patofizyolojisinde önemli rol oynarlar. Çalışmamızda, antioksidan ve glutatyonun öncüsü olan N-asetilsisteinin iskemi/reperfüzyonun böbreklerde oluşturduğu hasara karşı iyileştirici etkisinin olup olmadığını araştırmayı amaçladık. Gereç ve Yöntem: 24 adet dişi Sprague Dawley sıçan, 1. grup kontrol grubu, 2. grup İ/R grubu, 3. grup İ/R+NAC grubu olmak üzere, eşit sayıda 3 gruba ayrıldı. Kontrol grubuna intraperitoneal serum fizyolojik verildi. İ/R ve İ/R+NAC gruplarında, ksilazin-ketamin anestezisi altında her iki böbrek damarları klemp aracılığı ile kapatılarak, 60 dakika (dk) iskemi ve 24 saat reperfüzyon uygulandı. İskemiden 30 dk önce İ/R grubuna fizyolojik serum, İ/R+NAC grubuna 300 mg/kg N-asetilsistein intraperitoneal verildi. Kontrol grubunun fizyolojik serum enjeksiyonundan 24 saat sonra, İ/R ve İ/R+NAC gruplarının reperfüzyon döneminden sonra ksilazin-ketamin anestezisi altında kan örneği ve böbrek dokuları alındı. Böbrek dokusu süperoksit dismutaz, katalaz, glutatyon peroksidaz enzim aktiviteleri ile glutatyon ve malondialdehit düzeyleri; plazma üre, kreatinin, glutatyon ve malondialdehit düzeyleri belirlendi. Ayrıca böbrek dokusu histopatolojik olarak incelendi. Bulgular: İskemi/reperfüzyon grubunda; üre ve kreatinin düzeylerinin arttığı (p
Sıçanlarda Böbrek İskemi/Reperfüzyon Hasarında Nasetilsisteinin Etkileri